What are the spectroscopic properties of HFC‐32? Answers from DFT. Issue 21 (28th May 2014) - Tasinato, Nicola
<x xml:space="preserve">Abstract</x> Although coupled cluster theory coupled to large basis sets can reach impressive accuracies for thermochemical and spectroscopic properties, it is still limited to small/medium sized molecules. Density functional theory (DFT) represents the working option for systems composed of hundreds to thousands heavy atoms. In this context, investigations are required aimed at characterizing the performances of the different density functionals (DF). This work focuses on the study of DFT performances in the prediction of spectroscopic properties, with particular attention to the vibrational problem, by focusing on the CH2F2 molecule as a test case. An extensive and systematic investigation is performed on several DFT model chemistries by testing their predictions of molecular constants and vibrational frequencies and intensities against CCSD(T)/aug‐cc‐pCVQZ data. B3LYP, B3PW91, B97‐1, PBE0, TPSSh, M05, M05‐2X, and B2PLYP DFs are used in conjunction with a variety of basis sets. Anharmonic frequencies are derived from the VPT2 treatment of anharmonic‐ and hybrid CCSD(T)/DFT‐force fields. A software for VPT2 computations is also presented. © 2014 Wiley Periodicals, Inc.